Bibliometric Analysis of Employee Job Satisfaction: Exploring Under-Researched Variables - Deni Anggreani Sutomo (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study conducts a Systematic Literature Review (SLR) to identify underexplored variables influencing employee job satisfaction, map emerging research trends, and integrate psychological, organizational, and environmental factors into a comprehensive conceptual framework using bibliometric mapping. Methodology/Approach: This research applies the SLR method in strict accordance with the PRISMA 2020 guidelines. Relevant studies were retrieved from reputable scientific databases using structured keywords and Boolean operators. Bibliometric analysis using VOSviewer was employed to visualize the research density and interrelationships among variables. Results/Findings: The research predominantly focuses on traditional determinants such as compensation and leadership. Conversely, influential but under-researched variables, such as work-life balance, burnout, and self-efficacy, remain fragmented within low-density clusters despite their significant impact on overall satisfaction. Conclusions: The dominance of traditional determinants often overshadows critical low-density variables. Consequently, an integrative, multidimensional conceptual framework is essential to bridge existing research gaps and support holistic empirical investigations. Limitations: As this was a descriptive and bibliometric analysis, it did not assess causal relationships or provide longitudinal validation. Contributions: This study contributes to the literature by proposing an integrative conceptual model that unifies psychological factors, work-life balance, and organizational conditions, offering a strong foundation for future empirical research on employee well-being.